Appraisal of Groundwater Nitrate Accumulation in Faridkot and Firozpur District of South-Western Punjab - Yadav, Brijesh Kumar; Grover, Jagdish (Journal of Soil Salinity and Water Quality, 2023)
The study characterized nitrate concentration in groundwater of Faridkot and Firozpur district of Punjab and identified the pollution load of NO3 as a result of the groundwater using field surveys and analyses of chemical constituents. The electrical conductivity ranged from 0.24-10.50 dS m-1 in Faridkot and 0.28-8.70 dS m-1 in Firozpur district with mean of 3.51 and 1.93 dS m-1 in Faridkot and Firozpur tehsil, respectively. The groundwater in Jaitu tehsil of Faridkot district and Firozpur tehsil of Firozpur district contains higher residual sodium carbonate with mean value of 2.85 and 3.57 meq L-1. In Faridkot district the groundwater nitrate ranged from 0.09-1110 mg L-1 with average value of 502.16 mg L-1 in Faridkot tehsil followed by Kotkapura tehsil with average value of 52.78 mg L-1. However, in Firozpur district it ranged from 2.27 -87.34 mg L-1 with  average value of 39.77 mg L-1 in Firozpur tehsil followed by Guru Harsahai tehsils with average value of 25.11 mg L-1. On an average in Faridkot district 10%, 65% and 25% water samples having safe (150 mg L-1) limits of nitrate. However, on an average 8.03% and 91.97% water samples recorded safe (